Special issues of the contract of rent (demolition) of property - Trufanova, Yulia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The author investigates special peculiarities of agreement(contract) breach in case of material agreement terms violation. Special attention is paid to the above mentioned point in judicial practice.